2021
DOI: 10.1161/jaha.121.020917
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Midregional N‐Terminal Pro–Atrial Natriuretic Peptide and Soluble Suppression of Tumorigenicity 2 Levels on Heart Rhythm in Patients Treated With Catheter Ablation for Atrial Fibrillation: The Biorhythm Study

Abstract: Background We assessed the impact of preprocedural plasma levels of MRproANP (midregional N‐terminal pro–atrial natriuretic peptide) and sST2 (soluble suppression of tumorigenicity 2) on recurrence of atrial fibrillation (AF) at 1 year after catheter ablation of AF. Methods and Results This was a prospective, multicenter, observational study including patients undergoing catheter ablation of AF. MRproANP and sST2 were measured in a periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…A total of 8 studies were analyzed with 1,021 AF patients (including 255 AF recurrence and 766 not recurrence). The pooled analysis of 7 studies ( 14 , 19 , 20 , 22 , 26 , 31 , 33 ) as a continuous variable indicated that sST2 was associated with the risk of AF recurrence (HR:1.09, 95% CI: 1.02–1.16, P < 0.01; I 2 = 89.5% Figure 4 ). Sensitivity analyses showed that the outcomes were stable ( Supplementary Figure S4A ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…A total of 8 studies were analyzed with 1,021 AF patients (including 255 AF recurrence and 766 not recurrence). The pooled analysis of 7 studies ( 14 , 19 , 20 , 22 , 26 , 31 , 33 ) as a continuous variable indicated that sST2 was associated with the risk of AF recurrence (HR:1.09, 95% CI: 1.02–1.16, P < 0.01; I 2 = 89.5% Figure 4 ). Sensitivity analyses showed that the outcomes were stable ( Supplementary Figure S4A ).…”
Section: Resultsmentioning
confidence: 98%
“…Table 1 displayed the baseline characteristics of 24 included studies from 2015 to 2022, comprising 14 prospective studies ( 14 , 17 23 , 26 , 29 31 , 33 , 37 ), 4 retrospective studies ( 24 , 25 , 27 , 32 ), 4 cross-sectional studies ( 12 , 13 , 34 , 35 ), and 2 case-control studies ( 28 , 36 ). Eleven studies were conducted in Asia (China, Thailand, Singapore), 10 studies in Europe (Germany, Poland, Finland, France, Norway, Spain, Sweden, Turkey), and 3 study in America (The united states).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, some clinical studies have found that elevated ANP, or midregional N‐terminal pro‐ANP, type B natriuretic peptide, and N‐terminal pro‐BNP levels were significantly associated with the risk factor of AF recurrence after ablation. 54 , 55 , 56 , 57 , 58 We did not discuss the association between those factors and recurrent AF after ablation. Fourth, plasma corin levels are correlated with immediate heart rhythm, as confirmed by higher concentrations in AF than in sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…As abdominal visceral adiposity increases, there is a higher risk of noncalcified plaques [ 53 ]. A PARADIGM sub-study has demonstrated that plaque progression is also dependent on ageing [ 54 ].…”
Section: Physiopathological Mechanismsmentioning
confidence: 99%